The dual GLP-1/glucagon receptor agonist G49 mimics bariatric surgery effects by inducing metabolic rewiring and inter-organ crosstalk - M. Pilar Valdecantos; Laura Ruiz; Cintia Folgueira; Patricia Rada; Beatriz Gomez-Santos; Maite Solas; Ana B. Hitos; Joss Field; Vera Francisco; Carmen Escalona-Garrido; Sebastián Zagmutt; María Calderon-Dominguez; et al. (Nature Communications)
Abstract Bariatric surgery is effective for the treatment and remission of obesity and type 2 diabetes, but pharmacological approaches which exert similar metabolic adaptations are needed to avoid post-surgical complications. Here we show how G49, an oxyntomodulin (OXM) analog and dual glucagon/glucagon-like peptide-1 receptor (GCGR/GLP-1R) agonist, triggers an inter-organ crosstalk between adipose tissue, pancreas, and liver which is initiated by a rapid release of free fatty acids (FFAs) by white adipose tissue (WAT) in a GCGR-dependent manner. This interactome leads to elevations in adiponectin and fibroblast growth factor 21 (FGF21), causing WAT beiging, brown adipose tissue (BAT) activation, increased energy expenditure (EE) and weight loss. Elevation of OXM, under basal and postprandial conditions, and similar metabolic adaptations after G49 treatment were found in plasma from patients with obesity early after metabolic bariatric surgery. These results identify G49 as a potential pharmacological alternative sharing with bariatric surgery hormonal and metabolic pathways.